2003
DOI: 10.1055/s-2003-38666
|View full text |Cite
|
Sign up to set email alerts
|

Systematische Charakterisierung der sonomorphologischen Veränderungen in den Frühstadien der rheumatoiden Arthritis

Abstract: The FFT, MCP joints and ECU tendons are particularly important in systematic US screening of the hand for the purpose of establishing reliable evidence of inflammatory changes. Different stages of RA can be identified on the basis of the characteristic types of synovitis and the number of joints and tendons affected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…It is often reported that the sixth compartment (ECU) is frequently involved in RA [ 24 ], and Lillegraven et al report that tenosynovitis at this location can predict erosive progression in RA patients [ 2 ]. Intratendinous Doppler signal in the ECU in healthy participants has not previously been reported, but Doppler signals have been detected in healthy Achilles tendons [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is often reported that the sixth compartment (ECU) is frequently involved in RA [ 24 ], and Lillegraven et al report that tenosynovitis at this location can predict erosive progression in RA patients [ 2 ]. Intratendinous Doppler signal in the ECU in healthy participants has not previously been reported, but Doppler signals have been detected in healthy Achilles tendons [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…3, 4), 4/30 of the traumatic patients, and none of the control patients. The fluid in the patients with rheumatoid arthritis represents the inflammatory process of the synovium of the DIP joints [10], whereas the fluid in the trauma patients most probably represents acute trauma with fluid near the torn tendon. …”
Section: Discussionmentioning
confidence: 99%